Quality Variation Control for Three-Dimensional Wavelet-Based Video Coders. (18th February 2007) - Seran, Vidhya; Kondi, Lisimachos P.
Abstract : The fluctuation of quality in time is a problem that exists in motion-compensated-temporal-filtering (MCTF-) based video coding. The goal of this paper is to design a solution for overcoming the distortion fluctuation challenges faced by wavelet-based video coders. We propose a new technique for determining the number of bits to be allocated to each temporal subband in order to minimize the fluctuation in the quality of the reconstructed video. Also, the wavelet filter properties are explored to design suitable scaling coefficients with the objective of smoothening the temporal PSNR. The biorthogonal5 / 3 wavelet filter is considered in this paper and experimental results are presented for 2D+ t and t+ 2D MCTF wavelet coders.